Effects of a wholegrain-rich diet on markers of colonic fermentation and bowel function and their associations with the gut microbiome: a randomised controlled cross-over trial - Procházková, Nicola; Venlet, Naomi; Hansen, Mathias L.; Lieberoth, Christian B.; Dragsted, Lars Ove; Bahl, Martin I.; Licht, Tine Rask; Kleerebezem, Michiel; Lauritzen, Lotte; Roager, Henrik M. (Frontiers in Nutrition, 2023)
Background: Diets rich in whole grains are associated with health benefits. Yet, it remains unclear whether the benefits are mediated by changes in gut function and fermentation. Objective: We explored the effects of whole-grain vs refined-grain diets on markers of colonic fermentation and bowel function, as well as their associations with the gut microbiome. Methods: Fifty overweight individuals with increased metabolic risk and a high habitual intake of whole grains (~ 69 g/day) completed a randomised cross-over trial with two 8-week dietary intervention periods comprising a whole-grain diet (≥ 75 g/day) and a refined-grain diet (< 10 g/day), separated by a washout period of ≥ 6 weeks. A range of markers of colonic fermentation and bowel function were assessed before and after each intervention. Results: The whole-grain diet increased the levels of faecal butyrate (p = 0.015) and caproate (p = 0.013) compared to the refined-grain diet. No changes in other faecal SCFA, BCFA or urinary levels of microbial-derived proteolytic markers between the two interventions were observed. Similarly, faecal pH remained unchanged. Faecal pH did however increase (p = 0.030) after the refined-grain diet compared to the baseline. Stool frequency was lower at the end of the refined-grain period compared to the end of the whole-grain diet (p = 0.001). No difference in faecal water content was observed between the intervention periods, however, faecal water content increased following the whole-grain period compared to baseline (p = 0.007). Dry stool energy density was unaffected by the dietary interventions. Nevertheless, it explained 4.7 % of the gut microbiome variation at the end of the refined-grain diet, while faecal pH and colonic transit time explained 4.3 % and 5 %, respectively. Several butyrate-producers (e.g. Faecalibacterium, Roseburia, Butyriciococcus) were inversely associated with colonic transit time and/or faecal pH, whilst the mucin-degraders Akkermansia and Ruminococcaceae showed the opposite association. Conclusion: Compared with the refined-grain diet, the whole-grain diet increased faecal butyrate and caproate concentrations as well as stool frequency, emphasising that differences between whole and refined grains affect both colonic fermentation and bowel habits.